Arabic literary thresholds : sites of rhetorical turn in contemporary scholarship - Mūsawī, Muḥsin Jāsim.; Stetkevych, Jaroslav. (Middle East and Islamic Studies E-Books Online, Collection 2010, ISBN: 9789004223059., 2009)
This volume, dedicated to Jaroslav Stetkevych, includes a number of original contributions that signify a rhetorical shift in the social sciences and Arabic studies. The articles and essays deal with Orientalism, classical Arabic tradition, Andalusian poetry, Francophone literature, translation, architecture and poetry, comparative studies, and Sufism. Literary production is studied in its own terms to situate these literary concerns in the mainstream of cultural studies. The outcome is a solid and highly sophisticated scholarship that makes this book one of the most needed among scholars and students of comparative literature, Arabic poetics and politics, Orientalism, Afro-Asian studies, East/West encounters and translation.